Simulation study of the hydraulic transmitter-receiver system - Frąckowiak Damian (MATEC Web of Conferences, 2019)
The paper presents a hydraulic transmitter receiver system which is characterized by the ability to remotely send information utilizing a single hydraulic line. The system was subject to computer simulation in the software Fluid-SIM Hydraulics, and based on the obtained measurement results the influence of the parameters of its components on the correct operation of the entire system was determined.